On m-Sectorial Extensions of Sectorial Operators - Arlinskii, Yu.; Popov, A, (Журнал математической физики, анализа, геометрии, 2017)
We study maximal sectorial extensions of an arbitrary closed densely defined sectorial operator. In particular, abstract boundary conditions for these extensions are obtained. The results are applied for the parametrization of all m-sectorial extensions of a nonnegative symmetric operator in a planar model of two-point interactions.